A development of game engine : foreign exchange trading simulation game / Fazreil Amreen Abdul Jalil - Abdul Jalil, Fazreil Amreen (Faculty of Computer and Mathematical Sciences, 2007)
This report is a project report to a game engine development. The game engine is mainly about the foreign exchange trade. The rest of the report will discuss about the development of the game. The game engine will mainly play the control of the FOREX simulation and have total control of the simulation. The game engine will provide operations and data structures for the real game. FOREX knowledge is a field of knowledge that many do not bother to know. FOREX is important as we are competing financially with other nations in the market. Building a game engine may help other programmer to develop a game about FOREX